The Use Of Planning On Employees’ Performance At The Dprd Secretary Office In Medan - Wahdatun Thoibah; Nurbaiti Nurbaiti (Indonesian Journal of Multidisciplinary Science, 2021)
Planning is the process of achieving organizational goals, in order to achieve the goal of developing an organizational work activity plan. The budget is very important to do in order to be able to finance all the needs of the program that is run and its realization can be in accordance with the set budget. Meanwhile, performance is what is done and what is not done by the employee is the work that has been achieved by the employee. The purpose of this study was to determine the function of budget planning on the achievement of employee performance at the Secretariat of the DPRD City of Medan. In this study the author uses a qualitative research approach. Analyzing research data using primary data and secondary data, data collection techniques in the form of observations and interviews obtained from the Medan City DPRD Secretariat Office in 2021 show that the planning function towards the achievement of employee performance is positive and significant to the achievement of employee performance at the Medan City DPRD Secretariat Office.